Food loss and Waste Reduction as an Integral Part of a Circular Economy - Vilariño, Maria Virginia; Franco, Carol; Quarrington, Caitlin (Frontiers in Environmental Science, 2017)
One-third of food produced for human consumption is lost or wasted globally, which amounts to about 1.3 billion tons per year. An updated review of global food loss and waste (FLW) is presented, as well as the related environmental, social and economic impacts, based on existing data and peer-reviewed literature. The authors reflect on the different food waste patterns and challenges faced by diverse regions around the world. The scale of FLW throughout the food value chain is analyzed, from agricultural production down to household consumption and disposal. FLW represent a waste of resources used in each production stage, such as land, water and energy; FLW also contributes to unnecessary increase of greenhouse gas (GHG) emissions. The environmental and socio-economic impacts of FLW are analyzed based on reviewed life cycle assessments. Providing insights into key concepts around FLW, this article highlights the scale of the problem at a global and regional level. It also reflects on the main challenges for implementing strategies to reduce FLW and the implications for policy-making.